The Influence of Price, Facilities, and Location on Tourist Satisfaction at Padang-Padang Beach Tourist Attraction in Pecatu Village - PEBRIANATA, I Nyoman Hardita; SORAYA, Dewi; MAHARANI, Ida Ayu Dinda Priyanka (Journal Management and Hospitality, 2023)
This study examines and analyses the influence of price, facilities, and location on tourists' decision-making. The research was conducted at Padang-Padang Beach Tourist Attraction in Pecatu Village, involving 100 respondents selected using Slovin's formula. All data obtained from the distribution of questionnaires were deemed suitable for use and will be analyzed using multiple linear regression and hypothesis testing (t-test and F-test). The study's findings indicate that: 1) Price, facilities, and location significantly impact tourists' decision-making at Padang- Padang Beach Tourist Attraction in Pecatu Village. 2) Price positively and significantly affects tourists' decision-making at Padang-Padang Beach Tourist Attraction in Pecatu Village. This means the more aligned the offered price is with the quality provided, the more tourists' decisions will improve. 3) Facilities positively and significantly affect tourists' decision-making at Padang-Padang Beach Tourist Attraction in Pecatu Village. This indicates that the better the facilities provided, the more tourists' decisions will increase. 4) Location positively and significantly affects tourists' decision-making at Padang-Padang Beach Tourist Attraction in Pecatu Village. This means that the more strategic the business location, the more tourists' decisions will improve.